Diversity, structure and composition of pteridophyte in varying habitats in Karimun Besar Island, Riau Islands Province, Indonesia - Nery Sofiyanti; Dyah Iriani; Ikhwan Taufiq; Maya Sari; Andre Irawan; Farid M. Syauqi (Society for Indonesian Biodiversity, 2021)
Abstract. Sofiyanti N, Iriani D, Taufik I, Sari M, Irawan A, Syauqi FM. 2021. Diversity, structure and composition of pteridophyte in varying habitats in Karimun Besar Island, Riau Islands Province, Indonesia. Biodiversitas 22: 4847-4856. Biodiversity of small islands, particularly in tropical region, always encourages scientific curiosity. Such curiosity is much greater when the small island of interest has been through various land use changes, such as in Karimun Besar Island. This island is one of thousand islands in Riau Islands Province, Indonesia and poses different land uses. However, studies on the biodiversity of flora in this island have not been recorded, including for pteridophyte or fern members. This study aimed to examine the diversity, floristic structure and composition of pteridophyte at six different study sites in Karimun Besar Island representing varying habitat conditions (i.e., primary forest, secondary forest, rubber plantation, road side, coastal area and mined land. The sampling was collected by using transect method to measure density, dominance and frequency. A total of 32 species of pteridophytes were recorded from the six study sites that belong to two divisions, Polypodiophyta (31 species) and Lycophyta (1 species). The number of species of pteridophyte varied across the six habitats. The highest number of species (21) was found in primary forest, while the lowest (9 species) was found in rubber plantation. The dominant species for each study site were Taenitis blechnoides (Pteridaceae) (rubber plantation), Dicranopteris linearis (Gleicheniaceae) (secondary forest), Sticherus truncates (Gleicheniaceae) (primary forest), Pteridium caudatum (Dennstaedtiaceae) (road side), Achrosticum aureum (Pteridaceae) (coastal area) and Nephrolepis hirsutula (Nephrolepidaceae) (mined land). The result of this study provides the first data of fern in Karimun Besar Island that support pivotal information on the biodiversity of small islands in tropical region.